Magnetic resonance imaging of brain inflammation using microparticles of iron oxide. - McAteer, M; von Zur Muhlen, C; Anthony, D; Sibson, N; Choudhury, R (2011)
For molecular magnetic resonance imaging (mMRI), microparticles of iron oxide (MPIO) create potent hypointense contrast effects that extend a distance far exceeding their physical size. The potency of the contrast effects derive from their high iron content and are significantly greater than that of ultra-small particles of iron oxide (USPIO), commonly used for MRI. Due to their size and incompressible nature, MPIO are less susceptible to nonspecific vascular egress or uptake by endothelial cells. Therefore, MPIO may be useful contrast agents for detection of endovascular molecular targets by MRI. This Chapter describes the methodology of a novel, functional MPIO probe targeting vascular cell adhesion molecule-1 (VCAM-1), for detection of acute brain inflammation in vivo, at a time when pathology is undetectable by conventional MRI. Protocols are included for conjugation of MPIO to mouse monoclonal antibodies against VCAM-1 (VCAM-MPIO), the validation of VCAM-MPIO binding specificity to activated endothelial cells in vitro, and the application of VCAM-MPIO for in vivo targeted MRI of acute brain inflammation in mice. This functional molecular imaging tool may potentially accelerate accurate diagnosis of early cerebral vascular inflammation by MRI, and guide specific therapy.